Solid waste management case studies in Istanbul - Kemerburgaz and Bursa - Gecit - Polat, Uraz. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
The limited resources have been exhausting because of developed technology, growth of population, production and consumption gain all over the world. Nevertheless solid wastes, which human being caused, are one of the main factors in environmental problem. The large and increasing amounts of municipal solid wastes generated each year in several industrialized countries, have raised concerns about the economic viability and environmental acceptability of the current waste disposal methodologies. There are various options available to convert solid waste to energy. Mainly, the following types of technologies are available: sanitary landfill, incineration, gasification and anaerobic digestion. Sanitary landfill is the scientific dumping of municipal solid waste and landfill gas could be used for generating power. In this study, methods of solid waste disposed, and energy potential of the solid wastes were examined by giving Istanbul-Kemerburgaz application. In the first section of the thesis, the importance, aim and extent of the study was explained. In the second section definitions and evaluations about solid wastes were given. In the other sections integrated waste management, land filling and land fill gas as an energy resource were explained respectively. Istanbul-Kemerburgaz Project about waste to energy application was investigated in the seventh section of the thesis. According to the literature and Istanbul Project, a projection of potential of Bursa Gecit Sanitary landfill has been done in the eighth section. And in the last section results were evaluated. The main purpose of this study is to investigate the waste to energy implementation of Istanbul-Kemerburgaz Facility and apply the results to Bursa-Geçit Sanitary Landfill to estimate its gas and electricity potential. And to illustrate the progress on the management of municipal solid wastes to the prospective municipalities around, during the harmonization studies for the membership of Turkey to European Union.
Keywords: Salvage (Waste, etc.); Refuse and refuse disposal.